Analisis Profil Morfologi Prevotella intermedia Pascapaparan Hydrogel Dressing Berbasis Karagenan Alga Merah - Khuladista Nafla Favela (Fakultas Kedokteran Gigi, 2026)
Introduction: Prevotella intermedia is an obligate anaerobic Gram-negative bacterium implicated in the progression of periodontal disease. Periodontitis treatment includes administering antibiotics, scaling root planing, and surgical procedures that require periodontal dressing to cover the wound area. Synthetic polymer-based hydrogel dressing such as polyvinyl alcohol still exhibit limitations, including lack of antibacterial activity and poor mechanical properties. Therefore, carrageenan-based hydrogel dressing from red algae (K. alvarezii and Gracilaria) are being developed due to their stable gel-forming ability and potential antibacterial effects, which may influence bacterial morphology. Aim: To analyze the morphological profile of P. intermedia after exposure to red algae carrageenan-based hydrogel dressing. Methods: This experimental laboratory study consisted of four groups: negative control (aquadest), positive control (chlorhexidine 0,2%), and two treatment groups ((carrageenan hydrogel dressing of red algae K. alvarezii (P1) and Gracilaria (P2)). The bacterial morphology profile analysis test was assessed through 2 stages: a bacterial sensitivity test and a bacterial morphology profile test. Results: The negative control group showed no morphological changes. In contrast, the positive control and treatment groups (P1 and P2) demonstrated morphological profile changes, including changes in shape from rod to oval, solitary arrangements with some appearing in clusters, and changes in cell size. The positive control showed a decrease in cell length (33.34%) and an increase in width (87.27%). Similarly, group P1 showed a decrease in cell length (32.69%) and an increase in width (89.09%), while group P2 showed a decrease in length (32.05%) and an increase in width (90.91%). Conclusion: There were changes in the morphological profile of P. intermedia after being exposed to red algae kappa-carrageenan-based hydrogel dressing, including changes in cell shape, size, and arrangement.
Validasi dan Finalisasi Repositori File 25 Juni 2026_Kholif Basri
Keywords: Prevotella intermedia; morphological profile; hydrogel dressing; carrageenan; red algae